An investigation of satellite maneuvering and orientation strategies using an air bearing table - Kuhn, Eckhardt (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.